THE EFFECTIVENESS OF ACTIVE LEARNING VIDEO ENTITLED “SAYING SORRY“TO IMPROVE STUDENTS’ SPEAKING ABILITY IN LEARNING EXPRESSION OF APOLOGIZE - Yogie Agustina Nugraheni (Universitas PGRI Semarang, 2014)
The main objectives of this research are: (1) To find out the speaking ability of expressing apology of the students taught using active learning video; (2) To find out the speaking ability of expressing apology of the students taught without using active learning video; (3) To know some significant differences between the speaking ability of expressing apology of the students taught using active learning video and without using active learning video. In order to achieve the objectives of the study, relevant theories were referred and discussed. There were audio visual, video, speaking, expressions of apologize, and active learning video to improve speaking ability. This study was an experimental research. The population of the research was seventh year students of SMP N 2 Kedungtuban Blora. The 52 students were taken from two classes as the sample. The sample divided into two classes, they were experimental class and control class. Every class has 26 students. Post test only experimental design was used in this research. The instrument of this research was oral test. Before gave the test, The students in control class taught without using active learning video, and then in experimental class the students were taught using active learning video as a treatment. Based on the result of the post test, the mean score of post test in control class was 65, 69 , then in experimental class was 76. According to the mean of post test each class, the mean of experimental class was higher than control class. T-test formula was used to know the differences of the test have done. The result of t-test is 7,99 and the t table of 52 students was 1, 67 from the table signification 5% (0, 05), so it can be concluded that there is a significant different of students’ speaking ability who taught using active learning video and without using active learning video. It can be conclude that active learning video is effective used in teaching speaking of apologize. On the basis of the conclusions, several suggestions can be offered. The teacher may use active learning video in teaching speaking. The students may use video to improve their speaking ability.